Estimation of Sea Surface Salinity Concentration from Landsat 8 OLI Data in The Strait of Madura, Indonesia - Muhsi Muhsi; Bangun Muljo Sukojo; Muhammad Taufik; Pujo Aji; Lalu Muhamad Jaelani (Universitas Muhammadiyah Surakarta, 2022)
Remote sensing technique to estimate the sea surface salinity has been widely implemented in the seas of various regions. The interface between them was developed using a regression equation like the algorithm in previous research. However, the use of this algorithm for waters in Indonesia, especially in Madura Strait, still requires some adjustment since it is related to the characteristics of different areas in which the algorithm was developed. The development of an applicable local algorithm was performed by finding the best coefficient value in estimating sea surface salinity by considering the value of its lowest NMAE (Normalized Mean Absolute Error). By using salinity and in-situ Rrs(l) (Reflectance of remote sensing) data, we found that the coefficient for the slope was -0.0092, and the intercept was 1.4903. The developed algorithm produces higher accuracy than the existing algorithm, with an NMAE of 0.51%. This NMAE value is smaller than previous research, so this new model can be used to estimate sea surface salinity, particularly in Indonesian sea waters.